Desymmetrization of Symmetrical Triarylcarbinols: Synthesis of 7-Arylfluorenes and a C2-Symmetric Chiral BIFOL Phosphoric Acid - Someshwar, Nagamalla; Karthick, Muthupandi; Ramanathan, Chinnasamy Ramaraj (Synlett, 2017)
A simple and an efficient method for the synthesis of 7-arylfluorenes by intramolecular cyclization of the corresponding triarylcarbinols in the presence of the solid-acid catalyst NaHSO4/SiO2 has been developed. By using this method, a new chiral diol with a C2-symmetric bisfluorenyl unit, 7,7′-diphenyl-7H,7′H-5,5′-bibenzo[c]fluorene-6,6′-diol (BIFOL), having central chirality was synthesized in an optically active form from (S)-(–)-BINOL-3,3′-dicarboxylic acid. The absolute configuration of the chiral bisfluorene derivative BIFOL was ascertained by single-crystal X-ray analysis. Furthermore, a new chiral phosphoric acid was synthesized from BIFOL and evaluated for enantioselective transfer hydrogenation.
Keywords: benzofluorenes; ligands; asymmetric synthesis; triarylcarbinols; cyclization; transfer hydrogenation